ANALISIS KELAYAKAN USAHA KERUPUK BANDENG (STUDI KASUS: POKLAHSAR USAHA BUNDA) GAMPONG KUALA LANGSA, KECAMATAN LANGSA BARAT, KOTA LANGSA - Halisya Yuanda; Siti Balqies Indra; Muhammad Jamil (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
This research aims to determine the feasibility of Poklahsar Usaha Bunda's bandeng cracker business. This study is a case study conducted in Gampong Kuala Langsa, Langsa Barat Subdistrict, Langsa City. The data collected in this study includes both primary dan secondary data. To determine the feasibility of Poklahsar Usaha Bunda's bandeng cracker business, a financial feasibility analysis were conducted using Net Present Value (NPV), Internal Rate Of Return (IRR), Payback Period (PP), dan Profitability Index (PI). The research subject, Ibu Maimunah, is the owner of the business. Based on the results of the financial feasibility analysis, the results of this study are that Poklahsar Usaha Bunda’s bandeng cracker business obtained an Net Present Value (NPV) is IDR 40.733.137,34 which is greater than zero, the Internal Rate of Return (IRR) is 57,21% higher than the set interest rate, the Profitability Index (PI) is 1,83, which is greater than 1, dan the Payback Period is 1 year 8 months 8 day. Therefore, it can be concluded that Poklahsar Usaha Bunda's bandeng cracker business is feasible to continue.